Regional profiling of abnormal protein expression & post translational modifications in glioblastoma - Kocon, Artur (2019)
Glioblastoma is one of the most common brain tumours that is associated with poor prognosis and median survival of 12 to 15 months. Classed as WHO grade IV, glioblastomas are highly aggressive tumours that quickly proliferate and diffusely infiltrate surrounding brain tissue. Current treatments of glioblastoma are often ineffective and even with total resection, tumours recur with more aggressive sub-clonal populations of malignant cells. One of the main characteristics of glioblastoma is its highly heterogeneous nature and acquirement of somatic mutations advantageous to tumour growth and suppression of apoptotic pathways. Pathogenesis of malignant brain tumours as well as mode of its transformation to a more aggressive phenotype is still largely unknown. Although genomic studies in brain tumours have elucidated a plethora of genetic markers associated with the subtypes of the disease and identified key gene regulators, only a few have been utilised in a clinical setting. One of the emerging approaches to study glioblastomas is by investigation of the active proteome that drives the disease and contributes to its aggressive nature. Genomic and proteomic studies have suggested that genes and proteins are both selectively up and down regulated in various tumour regions. Furthermore, through activation of specific pathways via post translational modifications of proteins such as phosphorylation, glioblastomas create an intricate network of signalling pathways which favour tumour growth and proliferation. In this study, we aimed to investigate abnormal signalling across distinct tumour sites which include tumour core, tumour rim and invasive margin of glioblastoma. Using glioblastoma tumour tissue, we utilised a number of proteomic techniques to investigate abnormal protein expression and post translational modifications. We found that protein expression was highly variable and distinct amongst tumour regions with some key regulatory proteins such as cytosolic superoxide dismutase, microtubule associated protein two and protein-L-isoaspartyl methyltransferase being heavily downregulated. We have also observed significant changes in activation of transcription factors and kinases that could drive malignant progression of glioblastoma tumour. Furthermore, we have evaluated efficacy of cannabidiol and s-adenosylmethionine as therapeutic agents in inhibition of proliferation. Our findings indicate that cannabidiol could act via G-protein-coupled receptor 55 and serotonin receptor type 1A to elicit its antiproliferative effects. However, further studies are required to clarify efficacy and targets of these compounds.